Wound healing is aided by glutathione peroxidase, a selenoprotein (The Review of Diabetic Studies, 2024)
Background: A multitude of cellular and molecular pathways are involved in the intricate biological process of wound healing. Particularly important in reducing oxidative stress and facilitating cellular repair are selenoproteins, and more specifically glutathione peroxidases (GPXs). Injuries frequently cause increased reactive oxygen species (ROS), which can lead to oxidative stress and harm cells and slow the healing process. Neutrophils, inflammatory cytokines, and reactive oxygen species (ROS) are essential components of the inflammatory response that starts the repair process. Antioxidant systems like selenoproteins are necessary because excessive ROS can worsen tissue damage. Selenium, a vitamin that is crucial for proper protein function, may also play a therapeutic role in cancer treatment and wound healing.Aim: The goal of this research is to better understand the antioxidant processes, inflammatory pathway interactions, and therapeutic potential of selenoproteins as they relate to wound healing and oxidative stress-related problems. The usage of selenium-based chemicals to improve recovery and fight linked diseases like cancer is being investigated in the study, as are the consequences of selenium supplementation. Conclusion: Finally, selenocysteine, methylselenocysteine, and methylseleninic acid are only a few of the selenium compounds that have demonstrated promise as cancer treatments owing to their capacity to trigger cell death and influence important physiological functions. These chemicals have the potential to kill cancer cells by activating caspase pathways, which in turn release cytochrome c and cause DNA damage. Meliselenocysteine and other selenium-based chemicals do not depend on p53 to determine cell death, yet they are nevertheless effective against many different types of cancer cells. With dose-dependent cytotoxicity and normal cell sparing, methylseleninic acid in particular has shown encouraging anticancer effects across several cancer types. Their promise as cancer targeted therapeutics is expanding as more is learned about their action mechanisms and selenium compounds are synthesized better.